Pharmacological correction of no-reflow phenomenon in myocardial infarction treatment - T. Yu. Mamonova; V. A. Markov; V. V. Udut (Бюллетень сибирской медицины, 2009)
This article presents the research findings on the impact of carvedilol on the course of the necrosis myocardium focus and malone dialdegid concentration with patients, afflicted with acute myocardial infarction. The study proves that carvedilol slows down the necrosis focus formation and relieves the intensity of the no-reflow phenomenon as well as the oxydative stress, in case it is administered prior to the trombolytic therapy.